2018
DOI: 10.2807/1560-7917.es.2018.23.21.1800237
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A: an epidemiological survey in blood donors, France 2015 to 2017

Abstract: Since mid-2016, hepatitis A virus (HAV) outbreaks, involving predominantly men who have sex with men (MSM), have affected countries in Europe and overseas. In France, HAV screening of blood donations in 2017 revealed a HAV-RNA prevalence ca fivefold higher than during 2015–16 (4.42/106 vs 0.86/106; p = 0.0005). In 2017, despite a higher male-to-female ratio (5.5 vs 0.7) and the identification of MSM-associated outbreak strains, only one of 11 infected male donors self-reported being a MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Viral NAT screening parameters usually include HIV1/2, HBV and HCV [ 33 , 34 , 35 ]. Depending on local conditions, further screening for hepatitis A virus (HAV) [ 36 ], parvovirus B19 (PB19) [ 37 , 38 ], West Nile virus (WNV) [ 39 , 40 ], dengue virus (DENV) [ 41 ], Zika virus (ZIKV) [ 42 , 43 ] or hepatitis E virus (HEV) [ 44 , 45 ] is required.…”
Section: Safety Of Blood Productsmentioning
confidence: 99%
“…Viral NAT screening parameters usually include HIV1/2, HBV and HCV [ 33 , 34 , 35 ]. Depending on local conditions, further screening for hepatitis A virus (HAV) [ 36 ], parvovirus B19 (PB19) [ 37 , 38 ], West Nile virus (WNV) [ 39 , 40 ], dengue virus (DENV) [ 41 ], Zika virus (ZIKV) [ 42 , 43 ] or hepatitis E virus (HEV) [ 44 , 45 ] is required.…”
Section: Safety Of Blood Productsmentioning
confidence: 99%
“…These collaborations have shown to be effective in the 2016–2017 outbreak mostly affecting men who have sex with men (MSM). In the context of this outbreak, we previously reported increased frequency of HAV-RNA-positive blood donors in 2017 compared with 2015 and 2016 [2]. We hereby update this information and report a persistently higher number of HAV-infected blood donors throughout 2018.…”
mentioning
confidence: 57%
“…RNA curves obtained showed a maximum HAV RNA titer of 3.1 × 10 8 IU/mL whereby peak titers >10 7 IU/mL were common (6/10 donors). Earlier studies had reported an even higher RNAemia of 8.59 × 10 8 IU/ mL (16), but suggested lower typical peak titers (16,17). Although the early phase of infection was characterized by rapid exponential growth and a median estimated HAV doubling time of 17.5 (range 14.1-24.7) hours (Table ), the later phase often showed a more or less pronounced biphasic decrease, resulting in a skewed or shouldered RNA curve.…”
Section: Hav Biomarker Results For Donors Who Showed Seroconversionmentioning
confidence: 94%